Pengaruh FOMO, Shopping Lifestyle, dan Positive Emotion terhadap Impulse Buying pada Pengguna TikTok Shop - Wardatus Solikha; Hanafi Adi Putranto (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study examines how Fear of Missing Out (FOMO), Shopping Lifestyle, and Positive Emotion influence Impulse Buying among Generation Z users of TikTok Shop in Surabaya. Using a quantitative explanatory approach, data were collected from 250 respondents through an online questionnaire distributed via social media platforms. The constructs were measured using validated indicators and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.1. The findings reveal that FOMO has a positive and significant effect on Impulse Buying, indicating that urgency cues and limited-time offers effectively trigger spontaneous purchasing decisions. Positive Emotion also demonstrates a positive and significant influence, showing that pleasurable emotional experiences during live shopping reduce cognitive control and increase impulsive behavior. Conversely, Shopping Lifestyle exhibits a negative and significant effect, suggesting that individuals with higher shopping experience tend to be more selective and evaluative, thereby reducing impulsive tendencies. The study highlights the strong role of psychological pressure and emotional engagement in shaping consumer behavior within social commerce environments, offering practical insights for digital marketers in designing effective promotional strategies.